Розрізняльна здатність торговельної марки: до питання визначення поняття - Савич, С.; Savych, S. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті розглядається поняття розрізняльної здатності торговельної марки, яка відноситься до визначальних властивостей цього об’єкта інтелектуальної власності. Автор звертає увагу на невідповідність вітчизняного підходу розуміння розрізняльної здатності підходам Європейського Союзу та юрисдикційних органів його держав-членів. Запропоновано, виходячи з природи торговельної марки, поділяти розрізняльну здатність торговельної марки на абстрактну (властивість торговельної марки власне як позначення (знака, символу) вирізнятися на фоні будь-якого товару та сприйматися будь-якими особами) та конкретну (властивість торговельної марки вирізнятися на фоні конкретного позначеного нею товару (послуги) та сприйматися зацікавленими цим товаром (послугою) особами). The article deals with the concept of trademark’s distinctiveness, which refers to determining properties of this object of intellectual property. The author draws attention to the discrepancy between domestic understanding of the distinctive character of trade mark and approaches of the European Union. Based on the nature of trademark it has been proposed to divide the distinctiveness ability of this object of intellectual property into abstract and specific. Abstract distinctiveness has declared as suitability of the trade mark namely as sign (symbol) differ and perceived by anyone and satisfy the requirements of uniqueness (the ability to perceive and remember in the minds of unspecified persons through a single act of cognition) and self-sufficiency (be functionally independent from the goods). The specific distinctiveness is ability of trade mark to differ in the composition of the body (designation and designated by it a particular product (service) and perceived by concerned these goods (services) persons (average consumers).
Trade Mark’s Distinctiveness: the Issue of the Definition.
Keywords: торговельна марка; пересічний споживач; абстрактна розрізняльна здатність; конкретна розрізняльна здатність; trade mark; the average consumer; abstract distinctiveness; the specific distinctiveness